PEMAKAIAN BAHASA INDONESIA PADA MASYARAKAT PESISIR DI DESA PUGER WETAN KABUPATEN JEMBER (SUATU TINJAUAN ETNOGRAFI KOMUNIKASI) - Setyari, Agustina Dewi; Poedjosoedarmo, Soepomo; Wijana, I Dewa Putu (Sunan Kalijaga State Islamic University Yogyakarta, 2016)
Puger Wetan Village is one of coastal villages in Jember district. Puger Wetan is a multiethnic village of Javanese, Maduranese, Mandarese and Usingese. In order to communicate with each other, those etnics need a communicating language. That language is Indonesian language. Athough it’s not the main language, Indonesian is used in educational and goverment areas in Puger Wetan. This reasearch explores how Indonesia language is used within socio-cultural bacgrounds, including social economic system. This is a descriptive qualitative research. The data is analized with communication ethnography theory. This reasearch does not only analyze the language perspective (verbal and nonverbal) but also sociocultural perspective of local people, who used the language as an interactive tool. The communication component, in Poedjosoedarmo’s terms, is the word from the term of OOEMAUBICARA. The result shows that the use of Indonesian in the area of government is coneveyed at three occasions between spoker and hearer, (1) The meeting among government officials, (2) The meeting between government officials and the People, and (3) The meeting between government officials and the guest (unknown persons). The use of Indonesian in the realm of educations conducted at four points of utterances, namely (1) within the board of teachers, (2) with the parents, (3) with guest of other institutions, and (4) within the teaching and learning in the Classroom. Factors that leads to the use of Indonesian in the realm of governance and education are (1) an official situation and (2) a relationship between speakers who are not familiar to each other.